Effects of CO2 enrichment on metal bioavailability and bioaccumulation using Mytilus galloprovincialis. (August 2018) - Passarelli, M.C.; Ray, S.; Cesar, A.; DelValls, T.A.; Riba, I.
Abstract: The main aim of this study was to evaluate the bioavailability of metals related to CO2 enrichment on the mussels Mytilus galloprovincialis by metal's bioaccumulation analysis. Two sediment samples were selected and subjected to different pH levels. Concentrations of metals were measured in the overlying seawater and in the whole body of mussels exposed on the 7th, 14th and 21st days. Results showed that the CO2 enrichment in aquatic ecosystems cause significant ( p < 0.05) changes on the concentrations of Cu, Zn, Ni, Mn and As between the control pH and pH 7.0 after 7 days of exposure; and in the concentration of Fe at pH 6.0 using the RSP sediment. The multivariate analysis results showed that the increase in the bioaccumulation of some metals in mussels was linked to the acidification. It was concluded that many factors may interfere in the results when the acidification and bioavailability of metals are inquired. Highlights: This study addresses the effects of acidification in marine ecosystems using mussels. CO2 enrichment in the marine ecosystem increased significantly the concentrations of some metals; There was relationship between accumulation of metals in tissues of Mytilus galloprovincialis and the decrease of pH values; The increase in the bioaccumulation of Fe, Ni and Zn in the body of mussels is related to acidification;